2015
DOI: 10.1111/papr.12302
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Burden of Chronic Widespread Pain and Fibromyalgia in the United States

Abstract: Fibromyalgia subjects were characterized by the greatest disease burden with more comorbidities and pain-related medications, poorer health status, function, sleep, lower productivity, and higher costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
0
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 43 publications
5
53
0
8
Order By: Relevance
“…The findings likewise aligned with previous studies highlighting the health and economic burden of fibromyalgia, although not specific to the Japanese population. In particular, fibromyalgia has been associated with multiple comorbidities,4 as well as decreases in most aspects of HRQoL 8. Moreover, high direct costs, due to health care resource use, and indirect costs, due to unemployment and work productivity loss, have been ascribed to fibromyalgia 8,9,11,12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings likewise aligned with previous studies highlighting the health and economic burden of fibromyalgia, although not specific to the Japanese population. In particular, fibromyalgia has been associated with multiple comorbidities,4 as well as decreases in most aspects of HRQoL 8. Moreover, high direct costs, due to health care resource use, and indirect costs, due to unemployment and work productivity loss, have been ascribed to fibromyalgia 8,9,11,12…”
Section: Discussionmentioning
confidence: 99%
“…Among Portuguese women, fibromyalgia was negatively associated with all dimensions of HRQoL, and the largest decreases were observed for physical functioning, physical role functioning, and general health 7. US adults (aged ≥18 years) diagnosed with fibromyalgia reported poorer sleep quality and health status, as well as more severe pain, than those with or without chronic pain 8. Another study on US adults (aged 18–65 years) demonstrated that severity has an impact on degree of burden; those with severe fibromyalgia self-reported greater pain intensity and fatigue, with poorer sleep quality, HRQoL, and mental health (anxiety and depression), than those with either moderate or mild fibromyalgia 9.…”
Section: Introductionmentioning
confidence: 98%
“…Fibromyalgia is a relatively common condition with an estimated prevalence of 2.7% in the general population worldwide [3], causing substantial health, economic, and social burden [4]. At present, the diagnosis of fibromyalgia is mainly based on clinical symptoms and no unbiased biomarkers that can confirm it are known [1,2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…UU se considera que afecta a 100 millones de individuos. Esta situación genera un coste de 560 a 635 billones de dólares anuales entre costes directos e indirectos (28), entre los que se destacan los gastos médicos directos, la pérdida de ingresos, la pérdida de productividad, los pagos por compensación y los gastos por servicios legales.…”
Section: Figura 2: Representación Gráfica Del Aumento De Publicacioneunclassified
“…Auqnue el gasto sanitario derivado de la FM es mucho mayor en comparación con otros cuadros de dolor crónico, este elevado gasto no revierte en una mejoría en el estado de salud de los pacientes (28). Esta situación posiblemente es debida a las numerosas enfermedades concomitantes asociadas a la FM según relatan algunos textos científicos (30,31).…”
Section: Figura 2: Representación Gráfica Del Aumento De Publicacioneunclassified